Organizational Effectiveness: Systematic Literature Towards a Conceptual Framework - Ahmad, Amran; Furuoka, Fumitaka; Rasiah, Rajah (AEI Insights, 2023)
To survive in this highly competitive business era, every business organization has to ensure a solid strategic position in the market. Researchers and practitioners highlight that enhancing the organization's effectiveness is essential to secure a strategic place in this competitive business world. Organizational effectiveness refers to the organization's success rate in achieving its goals. But it takes work to ensure the effectiveness of the organization. Therefore, the present study reviewed 25 articles using a systematic literature review approach. Based on the review outcomes, the present study proposes a unique model indicating the factors that enhance the organization's effectiveness. Accordingly, the present study highlights that business intelligence as methods and tools that organizations employ to manage and analyse business information, organizational agility such as market capitalizing agility, and operational adjustment agility. Agility is the capacity of an organization to renew, adapt, and change, and a fast evolving, uncertain, unstable environment and an innovative organizational climate, which is known as a creative organizational environment, are the influencing factors that influence organizational effectiveness. This study offers a unique direction for managers of organizations on how to ensure a strategic market position in this volatile business environment through enhancing organizational effectiveness.